Prevalent clones of methicillin resistant Staphylococcus aureus strains in Pakistan by various typing techniques - Altaf, Naila (Annals of Pathology and Laboratory Medicine, 2015)
Staphylococcus aureus (S.aureus) is an important pathogen that causes infections in both hospital and community settings .The resistant to methicillin in S.aureus emerged in 1960s and since then the prevalence of Methicillin resistant S.aureus (MRSA) has been increasing globally. The increasing incidence of MRSA infections demands a quick and reliable characterization of isolates and investigation of clonal spread of clones in hospitals as well as in the community to generate information that helps health care professionals to implement appropriate measure to control these infections. To investigate the MRSA outbreaks, evaluation of transmission of MRSA strains and their evolution, bacterial typing techniques are important tools. The continuous surveillance and monitoring of presence of MRSA in community and hospital settings is important to make a clear understanding of dynamics of spread of MRSA to assist in controlling its dissemination. In this review the various typing techniques that have been used to type MRSA isolates from Pakistan have been discussed. This review also focuses on the various clones of MRSA that are reported in Pakistani community as well as in hospitalized patients